Sustainability Strategies of the Fédération Internationale de l’Automobile: Integrating the Sustainable Development Goal into Formula 1 - Kanza, Velidita Daracaesa Shafira; Trisnaningtyas, Januari Pratama Nurratri (Universitas Pakuan, 2025)
This study examines the strategies adopted by the Fédération Internationale de l’Automobile (FIA) in implementing the United Nations Sustainable Development Goals (SDGs) framework through Formula 1 racing. As one of the most influential non-governmental organizations (NGOs) in global motorsport, the FIA has integrated sustainability principles into its operational and advocacy activities. Using the Social Purpose NGO Framework by Teegen, Doh, and Vachani, this research analyzes the FIA’s dual approach—operational strategies focused on environmental management and advocacy strategies aimed at public awareness and policy engagement. The study employs a qualitative descriptive method based on secondary data from FIA reports, environmental strategy documents, and previous research from 2019 to 2023. The findings reveal that the FIA’s operational strategies include the transition to renewable energy, the use of biofuels, water conservation initiatives, waste reduction programs, and reforestation projects around race circuits. Meanwhile, its advocacy strategies involve public campaigns, partnerships with organizations such as Ocean Cleanup and UNEP, and initiatives like #WeRaceAsOne to promote climate action and gender equality in motorsport. Collectively, these efforts align with eight priority SDGs, including clean energy, responsible consumption, climate action, and partnerships for the goals. The study concludes that the FIA’s sustainability agenda demonstrates how international sports organizations can act as catalysts for global environmental awareness and sustainable innovation.